2018
DOI: 10.4236/abcr.2018.71001
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Birth Rate Determining Worldwide Incidence and Regional Variation of Female Breast Cancer

Abstract: Purpose: Urbanization, obesity and ageing associated with lifestyle changes (Westernized diet patterns, pollution, physical inactivity) have been proposed as the major contributing factors for the global rise in breast cancer (BCa) and have been the variables used to predict the future breast cancer rate. At the same time, socio-economic level, instead of birth rate, has been proposed for explanation of dramatic regional variations of breast cancer incidence. We sought to determine which factor plays the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Unique cell intrinsic molecular and gene signatures have been described in TNBC patients of African ancestry compared with other ethnicities. [35][36][37] These findings support the hypothesis that ethnicity and TNBC-specific biomarkers exist for early cancer detection and therapeutic sensitivities. 38,39 For example, using single-cell gene approaches, Azizi et al observed significant differences in gene signatures of BC PDX samples derived from Black and White patients.…”
Section: Utilizing Tnbc Pdx Models To Identify Genes and Signaling Pasupporting
confidence: 76%
“…Unique cell intrinsic molecular and gene signatures have been described in TNBC patients of African ancestry compared with other ethnicities. [35][36][37] These findings support the hypothesis that ethnicity and TNBC-specific biomarkers exist for early cancer detection and therapeutic sensitivities. 38,39 For example, using single-cell gene approaches, Azizi et al observed significant differences in gene signatures of BC PDX samples derived from Black and White patients.…”
Section: Utilizing Tnbc Pdx Models To Identify Genes and Signaling Pasupporting
confidence: 76%
“…Therefore, women at reproductive age have been especially susceptible to excessive fat storage from the perspective of evolutionary biology [ 44 ]. Birth rates are low in developed countries, but high in developing countries [ 64 , 65 ]. Nutrition stored in the form of fatness in females of developed countries, which is supposed to be used for successful reproduction, is simply kept without use, which increases body weight of females in the developed world.…”
Section: Discussionmentioning
confidence: 99%
“…5) Low fertility rates have been associated with cancer risks in both females and males [111][112][113]. Fertility rates in Australia and New Zealand are much lower than in many other countries.…”
Section: )mentioning
confidence: 99%